2015
DOI: 10.1016/j.actbio.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Porous nanofibrous poly(l-lactic acid) scaffolds supporting cardiovascular progenitor cells for cardiac tissue engineering

Abstract: Myocardial infarction (MI) is the irreversible necrosis of heart with approximately 1.5 million cases every year in the United States. Tissue engineering offers a promising strategy for cardiac repair after MI. However, the optimal cell source for heart tissue regeneration and the ideal scaffolds to support cell survival, differentiation, and integration, remain to be developed. To address these issues, we developed the technology to induce cardiovascular progenitor cells (CPCs) derived from mouse embryonic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 59 publications
2
59
0
Order By: Relevance
“…Polyethylenimine due to the presence of amine structural units is categorized as a polyamine. It is demonstrated that polyamines such as arginine, putrescine, spermidine, and spermine can interact with cellular components such as DNA which will enhance cell growth, endothelial gene expression, such as an increase in expression of VEGF, and angiogenesis similar to angiogenesis in cancer . In this experiment, scaffolds have been fabricated using the electrospinning technique.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylenimine due to the presence of amine structural units is categorized as a polyamine. It is demonstrated that polyamines such as arginine, putrescine, spermidine, and spermine can interact with cellular components such as DNA which will enhance cell growth, endothelial gene expression, such as an increase in expression of VEGF, and angiogenesis similar to angiogenesis in cancer . In this experiment, scaffolds have been fabricated using the electrospinning technique.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this notion, we previously showed porous and nanofibrous scaffolds to enhance cardiac differentiation over control non‐nanofibrous scaffolds. [ 29 ] CM delivery using NF microspheres without gelling property resulted in significantly lower enhancement in CM engraftment (3,4‐fold enhancement over CM only, unpublished data) compared to the approximately tenfold CM engraftment increase using the NF‐GMS hydrogel. Various hydrogels were reported to improve CM retention or protection, [ 28,30 ] but their improvements were not at the same level as NF‐GMS in this work.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the regenerative potential of certain cardiac cell types such as cardiomyocytes and cardiac progenitors, they are not appropriate for heart tissue engineering due to scarce sources, difficult isolation, and low proliferation rate (Ptaszek, Mansour, Ruskin, & Chien, ). Therefore, stem or progenitor cells including ESCs (Liu et al, ), iPSCs (Tan et al, ), and adult stem cells (Golpanian, Wolf, Hatzistergos, & Hare, ) are promising cell sources for producing cardiomyocytes. The addition of other cell types such as vascular and connective tissue elements, compared with constructs based on single‐cell culture, can enhance the survival and maturation of cardiomyocytes, promote the formation of vascular network, and strengthen the mechanical integrity (Caspi et al, ).…”
Section: Application Of Construction Strategies In Solid Organ Tissuementioning
confidence: 99%